SP0134 INTERLEUKIN-2 therapy in sle. (15th June 2017) - Humrich, JY
Abstract : There is an unmet need for more effective and selective therapeutics in severe autoimmune diseases such as systemic lupus erythematosus (SLE). A deeper understanding of the pathogenic mechanisms in the past has led to the clinical translation of low-dose interleukin-2 (IL-2) therapy which primarily aims to restore the activity of regulatory T cells. First results from phase I/II studies are promising by proving the selective expansion of regulatory T cells in vivo and by providing first evidence for the clinical efficacy of low-dose IL-2 therapy in SLE. Here we will summarize key findings which led to the development of this novel therapeutic concept and will highlight the main rationales for the clinical translation of low-dose IL-2 therapy in SLE. Disclosure of Interest: None declared